﻿Inhibitory effects of Moringa oleifera leaves extract on xanthine oxidase activity from bovine milk - Hasnah Natsir; Abdur Rahman Arif; Abdul Wahid Wahab; Prastawa Budi; Rugaiyah Andi Arfah; Arwansyah Arwansyah; Ahmad Fudholi; Ni Luh Suriani; Achmad Himawan (Pensoft Publishers, 2022)
Moringa oleifera is a tropical plant in the Moringaceae family that contains a lot of bioactive compounds. This study aimed to isolate and characterize the enzyme xanthine oxidase (XO), and conducted inhibitory tests on XO using methanol extracts of M. oleifera leaves. The xanthine oxidase enzyme isolated from bovine milk was characterized to determine the optimum pH, temperature, and substrate concentration. XO inhibition was evaluated by in vitro and in silico methods. The results of XO isolation and characterization of bovine milk showed the optimum conditions at pH 6.5, substrate concentration of 0.1 mM, and temperature 35 °C with an activity rate of 32.47 mU/mL; 21.55 mU/mL, and 21.94 mU/mL. Inhibition analysis results on methanol extract of M. oleifera leaves showed the highest activity decrease at the extract concentration of 160 ppm, with a relative inhibition value of 21.35%, while allopurinol as a positive control has a relative value inhibition of 61.21%. Relative value inhibition indicated the potential of M. oleifera leaves as a source of medicinal plants for gout sufferers. Additionally, a computational analysis was performed to observe the molecular interaction between the primary compounds of M. oleifera leaves, i.e., 5-O-acetyl-thio-octyl-β-L-rhamnofuranoside, quinic acid, and 2-dimethyl(trimethylsilylmethyl)silyloxymethyltetrahydrofuran, and XO using the molecular docking method. The finding implied that these compounds are bound to the catalytic sites of XO by hydrogen bonds and hydrophobic interactions, indicating the primary compounds of M. oleifera leaves could become XO inhibitors to treat gout disease.